Thermo-economic performance analysis and multi-objective optimization of viscosity ratio and thermal conductivity ratio of copper oxide-palm oil nanolubricants - Sofiah A.G.N.; Pasupuleti J.; Samykano M.; Rajamony R.K.; Pandey A.K.; Sulaiman N.F. (American Institute of Physics, 2025)
Through experimental research, this work explores the thermophysical properties, cooling efficiency, and economic viability of copper oxide-palm oil nanolubricants in tribology applications. The viscosity and thermal conductivity of the nanolubricants were tested at three different volume concentrations (0.1, 0.3, and 0.5 vol. %) throughout a temperature range of 30 C to 80 C at intervals of 10 C. Researchers looked attentively at how the viscosity and thermal conductivity ratios of the nanolubricants were affected by temperature and volume concentration. A significant increase in thermal conductivity was noted with increasing concentration and temperature. On the other hand, as temperature increased, viscosity reduced and was dependent on volume concentration. The property enhancement ratio was used to evaluate the nanolubricants' cooling capacity before an economic analysis of their cooling efficacy was conducted. Based on experimental data, the study led to the creation of novel correlations between the viscosity ratio and thermal conductivity ratio. These models showed a high degree of agreement (R2 values of 99.47% for the thermal conductivity ratio and 97.78% for the viscosity ratio) between the expected and actual outcomes. The ideal values of the viscosity and thermal conductivity ratios were 1.10 and 1.62, respectively. These values corresponded to a critical temperature of 37.32 C and a volume concentration of 0.16 vol. % for nanoadditives. The findings offer valuable insights into optimizing nanolubricants for enhanced cooling performance in tribological systems, with potential applications in improving energy efficiency and reducing operational costs in industrial processes. ? 2024 Author(s).